Teacher Performance of the State Vocational High School Teachers in Surabaya - Amiartuti Kusumaningtyas; Endang Setyawati (International Journal of Evaluation and Research in Education (IJERE), 2015)
Teacher Performance of the State Vocational High School Teachers in Surabaya   Dr. Amiartuti Kusumaningtyas, MM Faculty of Economics, 17 Agustus 1945 University, Surabaya, Indonesia Email: amiartuti.k@gmail.com Abstract State Vocational High School Teacher is a professional educator with major duties to educate, teach, build, direct, coach, assess and evaluate learners on the vocational high school education. Teacher as a professional educator should has the academic qualification. Academic qualification required for a teacher is he or she at least should be educated of bachelor degree or diploma four. Fundamentaly, teacher performance is determined by the expertise and ability of teacher concerned. These achievement factor is so thick and so critical in its relation to competence, compensation, and also job satisfaction that may become the obstacle in the enhancement of teacher performance. Population in this research was the teachers of the State Vocational High School Teachers in Surabaya, amounted to 317, educated in bachelor degree or diploma four, had have service of minimal 5 years. Data analysis used the simple random sampling, structural equation model (SEM) analysis, by the assistance of PLS 2 software, conducted on 92 respondents and able to explain the effect of competence and compensation on the job satisfaction and the performance of the State Vocational High School Teachers in Surabaya. The results of research indicated that: Competence and compensation significantly influential on teacher job satisfaction;  Competence and compensation significantly influential on teacher performance; Teacher Job satisfaction signifiacntly influential on the performance of the State Vocational High School Teachers in Surabaya. The largest effect of the three variables hipothesized on teacher performance in this research was the direct relatedness between compensation and teacher performance.   Key Words: competence, compensation, teacher job satisfaction, teacher performance